An improved numerical method for calculating mechanical properties of bi-modulus sandwich composite structures. (15th April 2022) - Qiu, Yu; Shen, Wei; Yan, Renjun; Li, Xiaobin; Ye, Zhenzhou; Li, Mengzhen; Liu, Kang; Qin, Kai
Abstract: Sandwich composite consists of panel material with higher strength and core material with lower strength, and the tensile elastic modulus and compressive modulus of these materials are often not equal. At present, the theoretical calculation and numerical calculation methods of bi-module materials are mainly applicable to single material and simple geometric structure, meanwhile, there will be situations such as slow convergence speed or even non-convergence of iterative algorithm. Therefore, when calculating sandwich composites, it is usually considered that the tensile modulus and compressive modulus are equal, which will bring great errors to the calculation. In order to better predict the cross-section characteristics and stiffness characteristics of bi-modulus sandwich composites, this paper developed the theoretical and numerical methods calculation methods suitable for bi-modulus sandwich composite structures. Example results show that the proposed finite element method based on field variables is consistent with the theoretical formula for bi-module materials, which can be used for structural design and safety check of marine sandwich composites. Highlights: A simple method was proposed to calculate the cross-sectional characteristics and load-bearing characteristics of typical sandwich composite structures. A improved method for analyzing the load-bearing capacity of sandwich composite materials considering the bi-modulus based on field variables was proposed. The typical examples of sandwich composite structure verify the effectiveness of numerical method.